Moral Education In Tamil Primary Schools In Malaysia: A Look Into Reality - Balakrishnan, Vishalache; Shoniah, Supramani (Penerbit Universiti Sains Malaysia, 2014)
The social issues and gangsterism rates among Indian adolescents have been in the rise in Malaysia over the last decade (Jabatan Siasatan Jenayah, Polis Diraja Malaysia, 2003). As academics in fields of humanities and language, the researchers writing this paper wanted to specifically initiate and analyse the teaching of Moral Education in Tamil vernacular primary schools in Malaysia. These subject has been questioned and brought up by educators and students involved in these schools. The issue is whether Moral Education (ME) is actually being implemented in Tamil Primary schools is looked into. This paper discusses the way ME is foreseen and being implemented in Tamil vernacular schools especially in Year 6 when students are prepared for their first centralised examination. It also looks into the effects of values education for Primary 6 Tamil students who move into another dimension of education when they are in Form One secondary classes.